Pale demon - Harrison, Kim (HarperVoyager, 2011)
Condemned to death for practicing witchcraft, bounty hunter Rachel Morgan is given three days to clear her name and get to the annual witches' convention in San Francisco, an effort that forces her to endure a cross-country drive with a motley crew of supernatural companions
Keywords: Morgan; Rachel; Occult fiction; Women bounty hunters; Witches; Vampires; Paranormal fiction; Demonology